In vitro Antimicrobial Activity of the Essential Oil of Ziziphora clinopodioides L. on Food Spoilage and Pathogenic Bacteria - M Mehraban Sangatash; R Karazhyan; S Beiraghi Toosi (Institue of Medicinal Plants, ACECR, 2007)
Background: The genus Ziziphora clinopodioides Lam. (Lamiaceae) are grown in most part of Iran. This plant has been used as an additive in yoghurt and other dairy products, but there is little study about antimicrobial activity of Ziziphora clinopodioides on food spoilage and pathogenic bacteria. Objective: The main goal of this study was to evaluate the antimicrobial activity of the essential oil of Ziziphora clinopodioides against some food spoilage and pathogenic bacteria and determine Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Method: Essential oil of Ziziphora (Ziziphora clinopodioides L.) was tested for itُ s growth inhibitory and bactericidal effect on 6 Gram-negetive (Enterobacter aerogenes, Escherichia coil, Klebsiella pneumoniae, Salmonella enteritidis, Pseudomonas aeroginosa and Shigella dysenteria) and 3 Gram-positive species (Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus). Minimum inhibitory concentration (MIC) was determined using dilution method and minimum bactericidal concentration (MBC) was taken from the concentration of the lowest dosed test tube showing no growth on subcultured. Result: All test organism were inhibited by Ziziphora clinopodioides L. except Pseudomonas aeroginosa and Shigella dysenteria. The MIC and MBC for Gram-negetive bacteria, including Enterobacter aerogenes, Escherichia coil, Klebsiella pneumoniae and Salmonella enteritidis were 250, 500, 125 and 250 μg/ml respctivily. The MIC for Gram-negetive bacteria, including Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus were 125, 1000, 125 μg/ml respctivily. Conclusion: It is concluded that essential oil of ziziphora has antimicrobial activity on food spoilage and pathogenic bacteria. According to the results of this study, It is applicable to use essential oil of Ziziphora as the natural preservatives and flavoring agents in food products.